Arquitetura bioclimática em proposta de projeto para complexo multiuso - FAGUNDES, Juliana Beatriz de Sousa (2023)
This undergraduate thesis in architecture and urbanism presents an architectural project proposal for a Multipurpose Complex in Ananindeua / PA. Its guidelines are the parameters of Bioclimatic Architecture. The architectural strategies were adopted based on the characteristics of the local climate. The project proposal was elaborated from the bibliographical research and case studies of multipurpose buildings that adopt as criteria solutions of thermal comfort (natural ventilation, natural lighting, green roof and sun shading system) and energy efficiency (photovoltaic plates and rainwater harvesting). It is also prioritized in the project the landscape proposals with the use of native plant species of the Brazilian Amazon, thus reducing excessive expenses with maintenance, fertilizers and chemicals. Thus, the architectural proposal presented has as its main objective to present a new concept of space attractive to city, which aims for the balance between architecture and the natural environment.